Developmental Politics in Transition
XVII, 329 p.
Keywords: Blending theory and case studies, this volume explores a vitally important and topical aspect of developmentalism, which remains a focal point for scholarly and policy debates around democracy and social development in the global political economy. Includes case studies from China, Vietnam, India, Brazil, Uganda, South Korea, Ireland, Australia.